Hubungan antara Obesitas dengan Keseimbangan Dinamis pada Lanjut Usia di Kelurahan Gonilan - Sentoso, Agil Mugi, Dwi Rosella K, S.St FT., M.Fis (2016)
Background: Obesity can be defined as overweight can ncrease the risk of the emergence of medical illness and premature death. Obesity accurs due to a higher energy intake than incurred. High energy intake cause by the consumption of high in fat an energy sources. Whereas low energy expenditure caused by lack of activity. Obesity may be related with dynamic balance, in the obese in terms of anatomy changes posture, what happens is the decrease range of motion, reduced elasticity of the ligaments and muscles, as well as the changing center of gravity. The impact of changes in posture can cause the body to become unstable. Research purposes: To know the relation between obesity and dynamic balance of the elderly people in Gonilan village Research benefit: To increase the knowledge, experience, and insight as well as materials in the application of research especially an overview of the relation between obesity and dynamic balance of the elderly people in Gonilan village search method: this research is observational with cross sectional approach. The sampling technique used is purposive sampling with 71 samples. The measurement of obesity uses BMI (Body Mass Index) whereas the measurement of dynamic balance uses TUG (Time Up and Go Test). The correlation test uses Chi Square Research finding: based on spearman rank test, it is known that p-value score is 0,000 < 0,005 so Ha is accepted it can be interpreted that there is correlation between obesity and dynamic balance of the elderly people in Gonilan village Conclusion: There is correlation between obesity and dynamic balance of the elderly people in Gonilan village